Screening Test penderita Malaria Dengan Gold Standar Uji Laboratorium Untuk Validasi Kasus Malaria Positif Di Wilayah Puskesmas Lewoleba Dan Puskesmas Waipukang Kabupaten Lembata, Propinsi Nusa Tenggara Timur Tahun 2016 - Ragu Harming Kristina (JURNAL INFO KESEHATAN, 2018)
Lewoleba Public Health Center and Waipukang Public Health Center are included in several Public Health Centers in Lembata District which show the high rates of malaria based on microscopic diagnosis methods. To see if there is a decrease in malaria cases, it is necessary to do a positive rate slide check to calculate the number of malaria positive patients. In order for the results of the examination to be truly valid, effective and efficient, it is carried out by a screening method to obtain True Positive and True Negative numbers, so that the results can be used as a database at the Public Health Center. This study aims to get a real picture of positive malaria cases after treatment, eradication and prevention efforts carried out by the government and donor sector. This type of research is a study of Analytical Epidemiology with screening methods and using a cross-sectional study design. Screening results of malaria sufferers in the Lewoleba Public Health Center with a sample of 600 people: True positive = 29 people, True negative = 555 people, Sensitivity (Sens) = 82.85%, Specificity = 98.20%, prevalence = 6, 51%. Screening results of malaria sufferers in Waipukang Public Health Center with a sample of 574 people: True positive = 537 people, True negative = 10 people, Sensitivity (Sens) = 95.8%, Specificity = 71.4%, prevalence = 94, 25%. The number of positive malaria cases in the Lewoleba Public Health Center work area was 29 people, while the positive malaria case in the Waipukang Public Health Center work area was 537 people.